Strategi Public Relation dalam Promosi Perpustakaan di Perpustakaan Daerah Kabupaten 50 Kota Payakumbuh - Manita, Rika Jufriazia; Wahyuni, Sri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study examines the public relations (PR) strategies implemented by the Department of Library and Archives of Payakumbuh City in promoting the library as an effort to strengthen the library's existence. Through a qualitative approach, this study analyzes various PR strategies used, including literacy campaigns, direct promotional activities, partnerships with schools and communities, and the use of social media. Data were obtained through in-depth interviews, observations, and document analysis. The results indicate that effective PR strategies can increase public awareness and participation in the library. However, there are several obstacles such as budget limitations and human resources constraints. This study provides recommendations for the development of more innovative and efficient PR strategies to enhance the library's role in improving literacy and the quality of education in the digital era. The findings are expected to serve as a reference for other libraries facing similar challenges.